Abortion crime in Poland - Smulski, Kamil (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
This chapter addresses issues related to the so-called abortion criminality (also often referred to as the ‘abortion underground’) in Poland, i.e., the phenomenon of aborting pregnancies in contravention of the law. The first part of the study concerns the issue of the diverse aetiology of this phenomenon. Next, an attempt was made to estimate the scale of the phenomenon. Moreover, manipulations in providing estimates related to the number of crimes of abortion against the provisions of the applicable law are also discussed. Then the author, referring to the aetiology, discusses the ways of counteracting the phenomenon of abortion criminality.